Abundance and Phylogenetic Analysis of High-Density Polyethylene (HDPE) Biodegrading Bacteria from Brantas River, Malang City - Wiratno, Ekwan Nofa; Sandra Wardani, Erika; Agustin, Nurmalita (Universitas Brawijaya, 2024)
Microplastic pollution has become a global concern after the COVID-19 pandemic. This requires efforts to resolve the various adverse effects of microplastic pollution in the aquatic environment. This study aimed to isolate, enumerate, and determine the potency of microplastic biodegrading bacteria from the Brantas River, Malang City. This research includes environmental factor measures, bacterial isolation, enumeration, biodegradation would be produced (qualitative and quantitative), DNA isolation, PCR, sequencing, phylogenetic analysis, and data analysis. The environmental conditions of the sampling locations are generally homogeneous. The river temperature observed ranged from 24.1 to 27.2 °C. Research locations that have acidity ranging from 7.35 to 8.16. The salinity of the Brantas River ranges from 205-306 ppm or 0.0205-0.306%. The conductivity of the Brantas River ranges from 410-612 µS/cm. Isolation produced six different bacterial isolates. The amount of each isolate varies in each sample. A qualitative microplastic biodegradation test was indicated by the growth of colonies in the plastic area. This result shows that the bacterial isolate uses plastic as a carbon source. All isolates grow around plastic. Quantitative tests using HDPE sheets show that not all isolates can biodegrade microplastics. Bacterial isolates capable of biodegrading were isolates K2 (5.41%), K22 (5.16%), and K5 (6.69%). Based on phylogenetic analysis, it is known that isolate K2 has a similarity of 36.4% to ON845428.1 Klebsiella sp. strain 214 37 z 3, and ON845427.1 Klebsiella sp. strain 213 37 z 1. Isolate K2 has a distance score of 1.268 to MZ642649.1 Klebsiella variicola strain PDW768. Isolate K22 has a similarity of 36.8% with KT895299.1 Enterobacter cloacae strain Jilu WG154. The distance score of isolate K22 showed values of 1.179 and 1.156 against MH796357.1 Enterobacter sp. strain 3C, and OQ813771.1 Enterobacter cloacae strain TBMAX59. Similarity and distance score values consistently showed that isolates K2 and K22 were not identified at the genus level. These two isolates have the potential to be recognized as new species.